Interest and Expectations for a Herpes Vaccine Among People Diagnosed with Genital HSV 1-2 Infection: Results from an Italian Survey - Lovel Lisac; Angelo Roberto Raccagni; Riccardo Lolatto; Flavia Passini; Chiara Maci; Elena Bruzzesi; Nicolò Moschetta; Antonella Castagna; Silvia Nozza (Viruses)
Genital herpes simplex virus (HSV) is associated with a reduction in quality of life and adverse outcomes. The aim of this study is to assess the interest and expectations for a therapeutic HSV vaccine among individuals diagnosed with genital herpes in Italy. A retrospective survey was conducted at the Infectious Diseases Unit of the IRCCS San Raffaele Scientific Institute, Milan, Italy. The study collected data on demographics, clinical history and interest in HSV vaccination. The results showed that 87.5% of participants were interested in a therapeutic vaccine, with interest higher among younger people and those with frequent genital herpes recurrences. Participants most expected the vaccine to reduce the pain associated with outbreaks, followed by a reduction in the frequency and duration of recurrences. These findings underscore the strong demand for a therapeutic HSV vaccine, especially among those who experience recurrent outbreaks, and highlight the importance of considering patient expectations when developing preventive and therapeutic strategies for genital herpes.